2011
DOI: 10.4103/0972-124x.92565
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive periodontal therapy

Abstract: Minimally invasive dentistry is a concept that preserves dentition and supporting structures. However, minimally invasive procedures in periodontal treatment are supposed to be limited within periodontal surgery, the aim of which is to represent alternative approaches developed to allow less extensive manipulation of surrounding tissues than conventional procedures, while accomplishing the same objectives. In this review, the concept of minimally invasive periodontal surgery (MIPS) is firstly explained. An ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 42 publications
0
12
0
4
Order By: Relevance
“…Evidence has shown that non-invasive or minimally invasive techniques to treat carious lesions are effective and must be preferred over surgical approaches, to avoid complex and expensive restorative therapies, increasing tooth function for longer years. [32][33][34][35] Latin American and Caribbean region countries should develop national public health programmes that include older people and that are based on systematic information on oral health needs and on effective interventions for achieving defined measurable goals. 15,36 Such public health programmes must not be confined to the treatment of the symptoms of the disease only, but must be appropriately designed to attain better oral health and quality of life for older people, including cultural adaptation.…”
Section: How Should the Actions Necessary To Improve The Oral Healtmentioning
confidence: 99%
“…Evidence has shown that non-invasive or minimally invasive techniques to treat carious lesions are effective and must be preferred over surgical approaches, to avoid complex and expensive restorative therapies, increasing tooth function for longer years. [32][33][34][35] Latin American and Caribbean region countries should develop national public health programmes that include older people and that are based on systematic information on oral health needs and on effective interventions for achieving defined measurable goals. 15,36 Such public health programmes must not be confined to the treatment of the symptoms of the disease only, but must be appropriately designed to attain better oral health and quality of life for older people, including cultural adaptation.…”
Section: How Should the Actions Necessary To Improve The Oral Healtmentioning
confidence: 99%
“…MID approach in endodontic procedures include: proper diagnosis, pulp tests utilization and caries risk protocol, minimally designed access opening, minimal removal of dentin, retention tooth structure during root canal instrumentation, utilize more crown lengthening procedure as opposed to tooth extraction and implant placement. If status of dental pulp allows the pulp protection procedure should be done as a definitive [16] .…”
Section: Endodonticsmentioning
confidence: 99%
“…Human adult PdSCs were isolated from patients with periodontal disease by minimally-invasive microsurgical surgery as described previously [46]. Minimally-invasive periodontal surgery had been shown to encounter several advantages [47]. Thus, such technique was used in all our experiments that required extraction of PdSCs from periodontal patients under surgery.…”
Section: Manipulation Of Pdscsmentioning
confidence: 99%